Hot-Fit Model to Measure the Effectiveness and Efficiency of Information System in Public Sector - Elvira Esperanza Sala; Apol Pribadi Subriadi (The Winners, 2022)
The research aimed to determine the effectiveness and efficiency of the information systems’ implementation. The research used the modified Human Organization Technology-Fit (HOT-Fit) as the model to measure information systems’ effectiveness and efficiency. Each indicator of the HOT-Fit model is mapped into two categories, namely effectiveness and efficiency. Data collection was conducted through interviews with the users of population administration information system (SIAK), and observation of activities at the public office. The data were analyzed qualitatively by assessing the achievement of each indicator of effectiveness and efficiency found in the interview and observation. It is found that effectiveness indicators are level of use, attitude, perceived usefulness, communication, availability, security, completeness, accuracy, timeliness, empathy, and transparency. Meanwhile, indicators to measure efficiency are users, training, staff support, ease of use, ease of learning, response time, access to technical support, and quick responsiveness. The research also expands the scope of the HOT-Fit model in evaluating information systems. Practically, the research can be a reference for evaluating the effectiveness and efficiency of information system implementation in the public sector. It also can be used to improve the achievement of indicators that have not achieved maximum results to improve services to the community.